Organisation and methods : a service to management - Milward, G. E. (London, Melbourne [etc.] Macmillan; New York, St. Martin's P., 1967)
A book on the ways and means of managing the office.
Includes bibliographical references and index.
oif 29/01/2019
Loans
Keywords: Office management; Organisation and methods